2020
DOI: 10.51791/njap.v46i3.864
|View full text |Cite
|
Sign up to set email alerts
|

Maize seed germination inhibition test for pregnancy diagnosis in Zebu cows

Abstract: Pregnancy diagnosis is an important part of good management and helps to maximizereproductive performance. Over time, different methods for detection of pregnancy in cows and other female domestic animals have been developed which include observation, physical examination, chemical tests and electronic instruments. Seed germination inhibition technique was carried out to detect pregnancy in Zebu cows. The urine samples collected from four pregnant cows, four non pregnant cows, four bulls and water (control) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Our findings support Lázničková et al (2020) who reported that the mean values were higher in DW than urine-water solutions regardless of the type of seeds used. The same trend is true for this study and the previous ones that used maize seeds in Zebu cows (Okunlola et al, 2019), dairy cows (Hussain et al, 2016), and heifers (Skálová et al, 2017), confirming that the mean germination and shoot length of maize seeds in DW is higher than that in urine-water solutions regardless of the breed or parity. Per contra, for each treatment group, there were variations in the figures between the current study and those reported in earlier studies (Rao Krishna and Veena, 2009;Rine et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings support Lázničková et al (2020) who reported that the mean values were higher in DW than urine-water solutions regardless of the type of seeds used. The same trend is true for this study and the previous ones that used maize seeds in Zebu cows (Okunlola et al, 2019), dairy cows (Hussain et al, 2016), and heifers (Skálová et al, 2017), confirming that the mean germination and shoot length of maize seeds in DW is higher than that in urine-water solutions regardless of the breed or parity. Per contra, for each treatment group, there were variations in the figures between the current study and those reported in earlier studies (Rao Krishna and Veena, 2009;Rine et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…This could be attributed to a lack of awareness of this technique and any other pregnancy detection techniques as is the case with other livestock farmers (Abigaba et al, 2022). The current higher mean germination and shoot length of maize seeds cultured in DW than that placed in urine-water solutions agreed with previous studies that used maize seeds (Okunlola et al, 2019) and other cereal seeds like wheat seeds (Rine et al, 2014;Skálová et al, 2017), and mung beans (Lázničková et al, 2020). Our findings support Lázničková et al (2020) who reported that the mean values were higher in DW than urine-water solutions regardless of the type of seeds used.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation